A day in the life of things in the home - Crabtree, Andy; Tolmie, Peter (2016)
This paper is about human interaction with things in the home. It is of potential relevance to developers of the Internet of Things (IoT), but it is not a technological paper. Rather, it presents a preliminary observational study of a day in a life of things in the home. The study was done out of curiosity - to see, given the emphasis on ‘things’ in the IoT, what mundane interaction with things looks like and is about. The results draw attention to the sheer scale of interaction with things, key areas of domestic activity in which interaction is embedded, and what it is about domestic life that gives data about interaction its sense. Each of these issues raises possibilities and challenges for IoT development in the home.